Ozone Monitoring Instrument (OMI) collection 4: establishing a 17-year-long series of detrended level-1b data - Q. Kleipool; N. Rozemeijer; N. Rozemeijer; M. van Hoek; J. Leloux; J. Leloux; E. Loots; A. Ludewig; E. van der Plas; D. Adrichem; D. Adrichem; R. Harel; et al. (Atmospheric Measurement Techniques, 2022)
The Ozone Monitoring Instrument (OMI) was launched on 15 July 2004, with an expected mission lifetime of 5 years. After more than 17 years in orbit the instrument is still functioning satisfactorily and in principle can continue doing so until the expected decommissioning of its platform Aura in 2025. In order to continue the datasets acquired by OMI and the Microwave Limb Sounder, the mission was extended up to at least 2023.